UTANG UNTUK RAKYAT - hudiyanto, hudiyanto (Jurnal Ekonomi & Studi Pembangunan, 2002)
Indonesia is the famous country that has a large amount of foreign debt. Until year 2000, Indonesia has the foreign debt about US$120 milliard, and it is more than psychological threshold (US$ 100 milliard). Some economist said that when the country has foreign debt more US$ 100 milliard, so the country is in the â€œdebt trapâ€ condition. Fisher also said if the country has the new foreign debt per year less than debt repayment per year, so the country is in â€œdebt crisisâ€ condition. This article will discuss about how Indonesia can exit from the debt crisis or debt? Did the foreign debt use for Indonesian people?